Generation of multiple spectral bands in a diode-pumped self-mode-locked Nd:YAP laser. (22nd December 2015) - Huang, Y J; Tzeng, Y S; Cho, H H; Chen, Y F; Chen, W D; Zhang, G; Chen, T C
Abstract: A single- and multispectral-band diode end-pumped self-mode-locked Nd:YAP laser is originally demonstrated with an intracavity etalon to properly control the gain-to-loss ratios among the intermanifold lines on the 4 F3/2   →   4 I11/2 transition level. With a pulse repetition rate of 5.07 GHz, the shortest pulse durations under the single-spectral-band operation are achieved to be 11.1 ps at 1073 nm, 10.9 ps at 1080 nm, and 15.1 ps at 1084 nm, respectively. Moreover, the temporal overlapping of the multispectral-band pulses is experimentally found to lead to the generation of an intensity fringe pattern in the autocorrelation trace with the optical-beat frequency reaching several terahertz. A simple mathematical model is developed to elucidate the formation of a train of optical-beat pulses.